Design Of Fiberglass / Aluminium Composite Dielectric Feed For Wideband Parabolic Antenna - Mohammad Amin, Nabila Husna (2017)
In conjunction with future development of technologies, current wireless systems available have not kept pace. The great interest in wideband systems is because the needed of high data rate wireless transmission and a wireless connectivity for longer range applications. With the latest technology, the microwave radio link device become smaller and cheaper, therefore, require an antenna which is not only small in size and reasonable price. This can be only achieved by using parabolic antenna. The typical parabolic antenna are using solid aluminium dish reflector and the gain is depending on the size of the reflector. Based on previous research a few techniques on enhancing the bandwidth such as using stacked DRA with microstrip line feed are applied in this works. This thesis describes the development of cylindrical dielectric resonator antenna fed for parabolic antenna. The implementation of stacked DRA, aperture coupling and the perforated DRA are shown in this research. The simulation is being done in CST microwave at first before the measurement is taking with network analyzer and signal analyzer. The simulation result of CDRA shows multiple resonant frequencies and provides a wideband of 60.71% after the techniques mentioned above is applied. This proposed work has operating frequencies in the range of 11 GHz to 22GHz. Then, the measurement of this CDRA feed for parabolic antenna is being done. A few parameters are taken into consideration. The experiment is carried out by comparing the proposed work with existing antenna which operated at 8.2GHz to 12.4GHz. xiv The results show that the gain of conventional antenna is better than the proposed antenna. If they be compared at 11.7 GHz the gain of conventional antenna is reported to be 7.6dB while the proposed work is at 9.2dB.